Microbiomic insights into the oral microbiome’s role in type 2 diabetes mellitus: standardizing approaches for future advancements - Guan, Huifang; Zhao, Shuang; Tan, Yuanfei; Fang, Xinyi; Zhang, Yuxin; Zhang, Yanjiao; Miao, Runyu; Yin, Ruiyang; Yao, Yiqi; Tian, Jiaxing (Frontiers in Endocrinology, 2024)
The burgeoning field of microbiomics has unveiled significant insights into the role of the oral microbiome in the pathophysiology of Type 2 Diabetes Mellitus (T2DM), with this review focusing on recent advancements in diabetic oral microbiology, its clinical applications, and identifying factors that may affect study interpretations. A comprehensive review across various databases, including PubMed and Google Scholar, was conducted to collate original research data published in the past five years, specifically targeting studies exploring the impact of the oral microbiome on T2DM and emphasizing research that employs microbiomic approaches in clinical patient populations. The findings delineate the intricate interplay between T2DM and oral microbiome dysbiosis, highlighting significant microbial shifts following periodontal and antidiabetic treatments, and pointing to the complexity of the relationship between oral health and systemic disease. The observed oral microbial shifts in T2DM underscore the critical need for standardized research methodologies in microbiomic studies, suggesting that by adopting a unified approach, future research can more effectively elucidate the oral microbiome's role in T2DM. This could pave the way for innovative diagnostic and therapeutic strategies in managing T2DM and its oral health complications, thus making a pertinent overview of the work within the field.